2012
DOI: 10.1007/s00125-012-2584-3
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between HbA1c levels and risk of cardiovascular adverse outcomes and all-cause mortality in overweight and obese cardiovascular high-risk women and men with type 2 diabetes

Abstract: Aims/hypothesis The optimal HbA 1c concentration for prevention of macrovascular complications and deaths in obese cardiovascular high-risk patients with type 2 diabetes remains to be established and was therefore studied in this post hoc analysis of the Sibutramine Cardiovascular OUTcomes (SCOUT) trial, which enrolled overweight and obese patients with type 2 diabetes and/or cardiovascular disease. Methods HRs for meeting the primary endpoint (nonfatal myocardial infarction, nonfatal stroke, resuscitated card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 36 publications
3
53
3
2
Order By: Relevance
“…The J-shaped trend conflicts with a recent observational study of a clinical trial conducted by Andersson et al who found no association between low HbA1c and increased mortality in overweight and obese patients not experiencing weight loss [8]. This could be caused by the difference in population groups between this study and the adjusted variables used in other studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The J-shaped trend conflicts with a recent observational study of a clinical trial conducted by Andersson et al who found no association between low HbA1c and increased mortality in overweight and obese patients not experiencing weight loss [8]. This could be caused by the difference in population groups between this study and the adjusted variables used in other studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Many clinical trials suggest a decrease in all-cause mortality as HbA1c values decrease [6][7][8], while others suggest that there is no association [9][10][11]. The debate has continued because of the early cessation of the Action to Control Cardiovascular Risk for Diabetes (ACCORD) trial [12], because there was an increased mortality in the treatment group that included patients who were trying to achieve low HbA1c levels.…”
Section: Introductionmentioning
confidence: 99%
“…Findings compared with previous studies Recent trials have found that intensive glucose control is associated with increased risk of cardiovascular death in younger patients [8] and observational studies have generally demonstrated Ushaped relationships between levels of HbA 1c in diabetic patients and death [28,29], possibly attributable to residual confounding through unmeasured variables [12]. In our study we adjusted for several important confounders, including comorbidities such as heart failure, chronic obstructive airways disease and chronic kidney disease.…”
Section: Discussionmentioning
confidence: 79%
“…A vérnyomás intenzív csökkentése szükséges, a célérték 140/85 Hgmm, amelynek szerepe van a micro-és macrosvascularis kockázat csökkentésében. A 130/80 Hgmm célérték esetén a stroke, retinopathia és albuminuria kialakulása csök-kenthető szelektált betegcsoport esetében [11].…”
Section: Diabetes Mellitusunclassified